HIPPMA Social Movement (Himpunan Pensiunan Perkebunan Maju Bersama) In Fighting For The Rights Of Retired PTPN II Workers - Christie Yosalin Manihuruk, Angela (Pusat Publikasi Nusantara, 2023)
Indonesia is one of the countries in the world that has a large number of workers. The increasing number of workers turns out to make conflicts between workers and companies more frequent. Not only workers, retired workers also experience problems with companies because their rights are not fulfilled. This paper analyzes and describes the social movement HIPPMA (Association of Plantation Pensioners Maju Bersama) to fight for the rights of retired workers. The research method used in this study is using a qualitative approach with a descriptive method. Data collection techniques are carried out by means of interviews and observations as well as literature studies and are interpreted based on the support of literature reviews so that a conclusion can be drawn. Theories about social movements and resource mobilization are used as analytical tools. The results showed that social movements are fundamental as a forum for workers to convey their aspirations. The difference between this HIPPMA organization and others is that the HIPPMA organization has a membership of PTPN II retirees and has different rights issues but they still fight together for these different rights. Social movements do not always reach destruction because in this HIPPMA organization they have high solidity and struggle for 20 years. Some of the successes of the HIPPMA social movement are already visible. The results that have been obtained are SHT (Old Age Compensation) for pensioners in 1991-1999 has been paid off by PTPN II, the issuance of BPN Decree number 42, 43, 44 / HGU / BPN / 2002 concerning Ministerial Decree 42 which issued 558.35 Ha of land for plantation pensioners. In addition, members of the HIPPMA organization have protection from the police, legal entities and government by issuing valid letters from the government so that retired plantations of the HIPPMA organization until now have not been evicted.